2020
DOI: 10.1021/acs.cgd.9b01568
|View full text |Cite
|
Sign up to set email alerts
|

Bis(phosphangulene)iminium Salts. Holding on to Fullerenes with Phangs

Abstract: Phosphangulene (“Phang”) is an analogue of triphenylphosphine with a conical shape and electron-rich aromatic surface that complements the electron-poor surface of fullerenes, both geometrically and electronically. Large molecular surfaces with multiple areas of concavity can be made by grafting units of Phang onto selected cores, using the ability of phosphorus to form covalent bonds with many other elements. Incorporating multiple conical subunits of Phang creates molecules that are awkwardly shaped, unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…Wuest et al reported X-ray crystal structures of various polymorphs of phosphangulene chalcogenides 116.2a – c 235 and those of the various solvates originating from the cocrystallization of 116.2a – c with C 60 or C 70 . 236 Furthermore, they characterized the crystal structures of the bis(phosphangulene)iminium salts (including [ 116.9 ][Br]) 237 and the silver(I) ( 116.10 + ) and copper(I) ( 116.11 + ) complexes featuring a metal center that is tetracoordinated by phosphangulene ( Scheme 116 ). 238 …”
Section: Pyrenoidsmentioning
confidence: 99%
“…Wuest et al reported X-ray crystal structures of various polymorphs of phosphangulene chalcogenides 116.2a – c 235 and those of the various solvates originating from the cocrystallization of 116.2a – c with C 60 or C 70 . 236 Furthermore, they characterized the crystal structures of the bis(phosphangulene)iminium salts (including [ 116.9 ][Br]) 237 and the silver(I) ( 116.10 + ) and copper(I) ( 116.11 + ) complexes featuring a metal center that is tetracoordinated by phosphangulene ( Scheme 116 ). 238 …”
Section: Pyrenoidsmentioning
confidence: 99%
“…Growth Des. 2020 , 20, 1319–1327 . A simple way to make molecules with large curved aromatic surfaces is to graft multiple units of phosphangulene onto suitable cores by exploiting the ability of phosphorus to form strong covalent bonds with other elements.…”
Section: Key Referencesmentioning
confidence: 99%
“…Molecules with large curved aromatic surfaces can be made by complex multistep syntheses, but a simpler approach is to graft multiple units of phosphangulene onto suitable cores by exploiting the ability of phosphorus to form strong covalent bonds with other elements. This strategy can be illustrated by synthesis of the bis­(phosphangulene)­iminium cation (abbreviated as [(Phang) 2 N] + ) . The related cation [(Ph 3 P) 2 N] + is widely used in chemistry, and over 1000 structures of its salts have been reported since the cation was first reported in 1961. [(Ph 3 P) 2 N] + has special properties that appear to arise from its globular shape and large aromatic surface. In particular, it is weakly coordinating, yields salts with enhanced solubility in organic solvents, facilitates crystallization, and stabilizes reactive anions.…”
Section: Using Phosphangulene and Derivatives To Bind Molecules With ...mentioning
confidence: 99%
See 2 more Smart Citations